Is small beautiful? farm size, productivity and poverty in Asian agriculture - Fan, Shenggen; Chan-Kang, Connie (Wiley, 2005)
Small farms characterize agriculture in Asia. With the fragmentation of land holdings, the average size of farms fell in the region, while the number of small‐size holdings increased significantly. These small‐scale farmers play an important role for food security and poverty alleviation. However, whether and how these small farms can survive under globalization is a hotly debated topic. In particular, the traditional claim that “small is beautiful,” which is based on empirical observation that small farms present higher land productivity than large farms, is being challenged. It has been shown that a positive relationship also exists between farm size and labor productivity (and therefore income). To help these small farms prosper under increasing globalization, the governments have to change the “business as usual” attitude. Innovative land reform, for example, is crucial to secure property rights to farmers and to increase farm size. Equally important is the reform of public institutions in order to help small farmers to have access to credit, marketing, and technology. Moreover, promoting diversification in the production of high‐value commodities can play an important role in raising the small‐holders' income. Finally, policies that facilitate urban–rural migration and promote the development of the rural nonfarm sector are essential to help alleviate poverty among small‐farm households and among the rural poor in general.